CADASIL: the most common hereditary subcortical vascular dementia. (November 2008) - Kalimo, Hannu; Miao, Qing; Tikka, Saara; Mykkäänen, Kati; Junna, Maija; Roine, Susanna; Viitanen, Matti; Pööyhöönen, Minna; Baumann, Marc
Cerebral autosomal dominant arteriopathy with subcortical infarct and leukoencephalopathy (CADASIL) is the most common hereditary subcortical vascular dementia. It is caused by the defective NOTCH3 gene, which encodes a transmembrane receptor; over 170 different mutations are known. The main clinical features are migraine with aura (often atypical or isolated), strokes, cognitive decline/dementia and psychiatric symptoms. Executive and organizing cognitive functions are impaired first, memory is affected late. Typical MRI findings are T2 weighted hyperintensities in temporopolar white matter and the capsula externa. Smooth muscle cells in small arteries throughout the body degenerate and vessel walls become fibrotic. In the brain, this results in circulatory disturbances and lacunar infarcts, mainly in cerebral white matter and deep gray matter. The exact pathogenesis is still open: a dominant-negative toxic effect is suggested, possibly related to Notch3 misfolding. Diagnosis is reached either by identifying a pathogenic NOTCH3 mutation or by electron microscopic demonstration of granular osmiophilic material in a (skin) biopsy. Only symptomatic treatment is available at present.